HOW TO BUILD CONFIDENCE IN VACCINES - Hannelie JC Meyer (International Journal of Infectious Diseases, 2023)
Despite overwhelming evidence of vaccine effectiveness in preventing serious vaccine preventable diseases (VPDs), lack of confidence in vaccines is a major threat to the prevention and control of VPDs and antimicrobial resistance globally. Vaccine hesitancy and antimicrobial resistance are inter-related, with high levels of vaccination uptake being a vital pillar of antimicrobial stewardship. Parallel with the COVID-19 pandemic, another ‘infodemic’ of uncertainty, misunderstanding, lack of trust and loss of confidence in vaccines unfolded. While regulatory authorities are mandated to ensure the safety, efficacy and quality of all approved vaccines, public confidence in vaccine safety and effectiveness is compromised by social media reports, falsely blaming vaccines for serious adverse events following immunisation. Hence, transparent public communication and education on vaccine safety; the risk-benefit balance; and causality assessment outcomes, are essential. A key factor in this context is people's perception of risk, especially where the fear of vaccines has replaced the fear of a VPD. Understanding the factors driving vaccine hesitancy and moving people from the point of being hesitant to the point of accepting vaccination, requires collective multi-pronged strategies from all levels of society, including political, social, religious and educational role players. Targeted approaches should be evidence-based, context-specific, culturally sensitive and tailored for the community, integrating individual, social and environmental factors. While healthcare professionals are the public's most trusted source of information for vaccination decision- making, they are not immune against believing misinformation and developing vaccine hesitancy. Consequently, they must be empowered with the necessary knowledge, skills and confidence to respond appropriately to questions and persuade the public to demand vaccination for themselves and their children. This presentation will focus on strategies to build vaccine confidence and acceptance, promote trust in the healthcare system, and address fears about the consequences of vaccination, aimed at driving vaccine uptake and preventing antimicrobial resistance.